2011
DOI: 10.2215/cjn.06130710
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bilirubin Links UGT1A1*28 Polymorphism and Predicts Long-Term Cardiovascular Events and Mortality in Chronic Hemodialysis Patients

Abstract: SummaryBackground and objectives Bilirubin is a protective factor with antioxidant and anti-inflammatory properties, but its association with clinical outcomes of hemodialysis patients is unknown. Bilirubin degradation is mainly determined by the activity of hepatic bilirubin uridine diphosphate-glucuronosyltransferase (UGT1A1), which is significantly influenced by a TA-repeat polymorphism in the gene's promoter, an allele designated UGT1A1*28. The study aimed to clarify the association between serum bilirubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 31 publications
3
62
1
1
Order By: Relevance
“…Epidemiological studies report that individuals with elevated UCB are protected from the development of intimal hyperplasia, atherosclerosis and cardiovascular disease (CVD) [1][2][3][4][5][6][7]. Furthermore, higher UCB concentrations (in the absence of haemolytic or liver disease) are associated with reduced incidence of CVD-related mortality [8][9][10][11][12]. The mechanisms responsible for CVD protection are not clear, however may be related to the potent antioxidant properties of UCB, given the potential role of oxidation in the development and progression of atherosclerosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies report that individuals with elevated UCB are protected from the development of intimal hyperplasia, atherosclerosis and cardiovascular disease (CVD) [1][2][3][4][5][6][7]. Furthermore, higher UCB concentrations (in the absence of haemolytic or liver disease) are associated with reduced incidence of CVD-related mortality [8][9][10][11][12]. The mechanisms responsible for CVD protection are not clear, however may be related to the potent antioxidant properties of UCB, given the potential role of oxidation in the development and progression of atherosclerosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cohort studies have shown that homozygosity for the UGT1A1*28 allele is associated with a much lower risk of CVD events. 15,16 UGT1A1*28 is not associated with conventional CVD risk factors 12,13 but has been linked to a significantly smaller brachial artery diameter and increased cold pressor test reactivity in young people, suggesting a beneficial influence on the size and structure of arteries. 3 Thus, serum bilirubin level may be an independent marker for environmental and genetically determined CVD risk.…”
mentioning
confidence: 99%
“…Our study restricting to patients with diabetes yielded the consistent results; however, the previous study used conventional Kaplan-Meier survival analysis and Cox proportional hazard model for estimating the event-free survival and hazard ratio, despite the presence of competing risks including kidney transplantation and losses to follow-up. These classical survival analyses have been shown to be inappropriate in the presence of competing risks, yielding the potential for biases [22]. To overcome these limitations, we used competing risks analysis and confirmed that the inverse association of serum bilirubin and ASCVD-related mortality was robust.…”
Section: Discussionmentioning
confidence: 84%
“…Total bilirubin levels and the bilirubin-associated UGT1A SNPs tended to be associated with all-cause mortality in patients with type 2 diabetes without kidney disease [25]. Furthermore, the above Taiwanese cohort study of hemodialysis patients showed that UGT1A1 gene polymorphism had strong effects on serum bilirubin levels and also influenced the incidence of ASCVD and all-cause mortality [22]. These clinical studies strongly implicate lower levels of bilirubin in the pathogenesis of ACSCVDs through increased oxidant properties.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation